Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.26668/businessreview/2023.v8i7.2977
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transformational Leadership, and Knowledge Sharing on Innovative Work Behavior of Public Organization in the Digital Era

Vita Mayastinasari,
Bayu Suseno

Abstract: Purpose: This study aims to analyze the role of Transformational Leadership on Innovative Work Behavior, and Transformational Leadership on Knowledge sharing and Knowledge sharing on Innovative Work Behavior of Public Organizations in the digital era.   Design/Methodology/Approach: This research uses quantitative research methods. The dimensions of transformational leadership are idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration). & The variable dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Similarly, Gul et al (2023) noted that transformational leaders encourage both explicit and tacit knowledge sharing, crucial for project success, by nurturing trust and openness. Mayastinasari and Suseno (2023) highlighted that while transformational leadership boosts knowledge sharing and innovative behaviour in public organisations, the direct impact of tacit knowledge sharing on innovation may vary based on organisational context and job nature. Building on these findings, the proposed research hypothesis is: H1: Transformational leadership has a significant influence on tacit knowledge sharing.…”
Section: Relationship Between Transformational Leadership and Tacit K...mentioning
confidence: 99%
“…Similarly, Gul et al (2023) noted that transformational leaders encourage both explicit and tacit knowledge sharing, crucial for project success, by nurturing trust and openness. Mayastinasari and Suseno (2023) highlighted that while transformational leadership boosts knowledge sharing and innovative behaviour in public organisations, the direct impact of tacit knowledge sharing on innovation may vary based on organisational context and job nature. Building on these findings, the proposed research hypothesis is: H1: Transformational leadership has a significant influence on tacit knowledge sharing.…”
Section: Relationship Between Transformational Leadership and Tacit K...mentioning
confidence: 99%
“…The development of this system is an innovative that makes it easier for users to monitor the DCFF process either from the perspective of collection and distribution]. Therefore, this is an innovative behavior is an individual behavior that aims to explore and promote new and useful ideas, processes, products or procedures (Mayastinasari & Suseno, 2023).…”
Section: Initiative Of the Governmentmentioning
confidence: 99%
“…To date, a plethora of research has discussed the antecedents of TW, including individual traits, contextual features and resources variables (Liu et al, 2020;Jiang, 2017;Spreitzer et al, 2012;Zeng et al, 2020). Leadership, as an organizational contextual feature and a provider of resources in the workplace (Deng et al, 2023;Mayastinasari and Suseno, 2023;Shah et al, 2023), has attracted researchers' attention in predicting employees' TW. Previous research has confirmed that leadership styles providing relational resources, such as authentic leadership (Mortier et al, 2016;Xu et al, 2017), servant leadership (Walumbwa et al, 2018), ethical leadership (Rahaman et al, 2022) and inclusive leadership (Zeng et al, 2020), promote TW.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership, as an organizational contextual feature and a provider of resources in the workplace (Deng et al. , 2023; Mayastinasari and Suseno, 2023; Shah et al. , 2023), has attracted researchers’ attention in predicting employees’ TW.…”
Section: Introductionmentioning
confidence: 99%